Protección de Datos Personales, ¿Responsabilidad de la Empresa? - Touriño Peña, Alejandro (2018)
On this occasion, ADVOCATUS had the opportunity to interview Alejandro Touriño Peña, leader of the European Personal Data Protection Law field. Throughout the following interview, we offer an analysis of the European Union regional regulations, protection measures offered, addressing the issue from the perspective of Corporate Responsibility, culminating in the analysis of a practical case.